Putusan Arbitrase sebagai Alternatif Penyelesaian Sengketa Perdagangan dalam Pembahasan Umum - Rahmadhani, Nisfi; Marpaung, Devi Siti Hamzah; Apriani, Rani (Peneliti.net, 2026)
The growing and increasingly complex nature of trade activities has the potential to cause disputes between the parties involved. Such disputes can be resolved through litigation or non-litigation mechanisms. Arbitration, as a form of non-litigation dispute resolution, offers an alternative that is considered more effective, efficient, and maintains the confidentiality of the parties. This study aims to examine the mechanism of arbitration in the resolution of trade disputes in Indonesia and the legal basis underlying it. The research method used is normative legal with a literature approach based on primary and secondary legal materials. The results of the study show that arbitration is carried out based on a written agreement between the parties, either through an arbitration clause in the main agreement (pactum de compromittendo) or a compromise deed made after the dispute occurs. Arbitration awards are final, binding, and enforceable, and can be enforced through the District Court in accordance with the provisions of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution.